A Robust Color Image Watermarking Scheme Using Entropy and QR Decomposition - Anbarjafari, Gholamreza; Laur, Lauri; Rasti, Pejman; Agoyi, Mary (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2015)
Internet has affected our everyday life drastically. Expansive volumes of information are exchanged over the Internet consistently which causes numerous security concerns. Issues like content identification, document and image security, audience measurement, ownership, copyrights and others can be settled by using digital watermarking. In this work, robust and imperceptible nonblind color image watermarking algorithm is proposed, which benefit from the fact that watermark can be hidden in different color channel which results into further robustness of the proposed technique to attacks. Given method uses some algorithms such as entropy, discrete wavelet transform, Chirp z-transform, orthogonal-triangular decomposition and Singular value decomposition in order to embed the watermark in a color image. Many experiments are performed using well-known signal processing attacks such as histogram equalization, adding noise and compression. Experimental results show that the proposed scheme is imperceptible and robust against common signal processing attacks.
Keywords: Chirp Z Transform; Color Image Watermarking; Discrete Wavelet Transform; Orthogonal-triangular decomposition; QR decomposition; Singular Value Decomposition